A critical review and analysis of Amlapitta from Samhitas - Radhika, Sahu Hrishikesh; Dipali, Swami (International Research Journal of Ayurveda & Yoga, 2022)
Amlapitta is very common disease in present era. Amlapitta is a life-style related disease prevalent all over the world. Amlapitta is disorder caused by habitat, irregular diet schedule and acivities but also as a result of Psychological and physiological observation. As the life is becoming very fast and the rate of urbanisation is growing. Pitta has been vitiated uses food and drink that are incompatible, spoiled, and very sour and that is capable of causing vitiation of pitta and increase drava and amlaguna of pitta. Aacharya Kashyapa has mentioned as the involvement of three Doshas in Amlapitta while Madhavkara has mentioned that the pitta is dominant in this disease. Aacharya Charaka has not mentioned Amlapitta as a separate disease but as a symptom. Aacharya Charak has described amlapitta in Granhi (intermittent loose motions followed by constipation) as one of its Lakshana (symptom). Various acharyas has explained amlapitta in different way with all nidan panchak of this disease but Samprapti of Amlapitta is clearly mentioned in Grahani chikitsa adhyay while describing samprapti of Grahani Dosha. The basic principle of treatment is mainly nidana parivarjana, shodhana, and shamana chikitsa. Vamana and Virechana are mentioned for urdhva gati and adho gati of doshas along with pathaya- pathaya of amalpitta.